2008
DOI: 10.1136/jme.2007.023374
|View full text |Cite
|
Sign up to set email alerts
|

Information and consent for newborn screening: practices and attitudes of service providers

Abstract: When the results of this survey are considered in conjunction with existing evidence there appears to be a consensus that good quality information in the prenatal period should be an integral part of any NBS programme. The issue of consent is more complex and there is less agreement on the preferred degree of parental involvement in decisions to allow babies to undergo NBS. A policy that both strongly recommends NBS but also allows parental choice appears to be most consistent with the views of LMC in this sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 25 publications
2
49
0
Order By: Relevance
“…Our findings are congruent with previous research that noted that the issue of consent is complex, with little consensus on the amount of parental involvement required for screening. 6,30,31 Other studies reported that providers who viewed obtaining consent as relatively easy (eg, midwives) appeared to favor an informed consent approach, in contrast to many providers who saw the process as time consuming and impractical (eg, pediatricians). 6 Meaningful parental understanding about NBS is a prerequisite for informed consent, but the importance of education is relevant even where screening is mandated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are congruent with previous research that noted that the issue of consent is complex, with little consensus on the amount of parental involvement required for screening. 6,30,31 Other studies reported that providers who viewed obtaining consent as relatively easy (eg, midwives) appeared to favor an informed consent approach, in contrast to many providers who saw the process as time consuming and impractical (eg, pediatricians). 6 Meaningful parental understanding about NBS is a prerequisite for informed consent, but the importance of education is relevant even where screening is mandated.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 To date, the literature concerning consent and newborn screening has generally focused on attitudes toward consent policy. 7,[25][26][27][28][29] Although this is revealing, occasionally showing conflicting attitudes toward the need for consent, 6,30,31 there is a lack of descriptive research that depicts how the offer of NBS is made to parents, making it difficult to determine the experience of consent in practice. Understanding the experiences of those actually involved in the consent process may provide valuable descriptive information for NBS programs and providers.…”
Section: Introductionmentioning
confidence: 99%
“…This has been shown to result in health professionals assuming that it is someone else's responsibility. 69,71 These issues appear to feed into another narrative in the data about who is responsible for ensuring that parents have the relevant information. Hayeems et al 61 found that health professionals recognised their responsibility to provide parents with information by signposting, but felt that it was the responsibility of parents to educate themselves.…”
Section: Relevant Informationmentioning
confidence: 99%
“…Interestingly, even health professionals have reported that parents do not receive any information. 69 Although their study took place in a research setting, Hargreaves et al 70 showed that midwives would sometimes select not to give women leaflets if they felt that they would not be able to understand them or appeared uninterested. Also, if parents were having their second or subsequent child, either party may have assumed that they already had knowledge and so NBS information was not given.…”
Section: Relevant Informationmentioning
confidence: 99%
“…While the knowledge regarding parental understanding, preferences, and satisfaction toward NBS education during the prenatal period is growing [6][7][8][9][10] and, in many cases, the lack thereof is explicitly criticized [11], the attitudes and reflections of health professionals on parental education and informed consent for NBS remains under-investigated [12]. This paper presents the findings of an empirical study exploring the views of officials and practicing physicians involved in the NBS process in Israel regarding issues of informed consent and parental education.…”
Section: Introductionmentioning
confidence: 99%